2003
DOI: 10.1067/mva.2003.177
|View full text |Cite
|
Sign up to set email alerts
|

R136K fibroblast growth factor-1 mutant induces heparin-independent migration of endothelial cells through fibrin glue

Abstract: Site-directed mutagenesis of FGF-1 to R136K enables induction of heparin-independent migration of EC through fibrin glue at an optimal concentration of 100 ng/mL. Neither FGF-1 nor R136K elicits SMC migration through fibrin glue. The ability of R136K to induce EC migration through fibrin glue in the absence of heparin may prove useful in vivo by inducing EC migration and coverage of arterial injury sites, thus potentially reducing thrombogenicity and intimal hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…[33] In another study by the same group, the dose effect of the non-glycosylated BMP-2 was found with significant differences between 2 and 5 μg of non-glycosylated BMP-2 but no such difference between 5 and 10 μg. [34] Modification of factors can extend beyond affecting solubility, as shown in two studies by Erzurum et al[35] and Shireman et al[36], where two different mutations of FGF-1 reduce the susceptibility of the growth factor to cleavage by thrombin and thus extend its duration of bioactivity. This is especially important in drug delivery utilizing fibrin glue due to the high levels of thrombin used to form the gel.…”
Section: Loaded Factor Drug and Vector Systemsmentioning
confidence: 99%
“…[33] In another study by the same group, the dose effect of the non-glycosylated BMP-2 was found with significant differences between 2 and 5 μg of non-glycosylated BMP-2 but no such difference between 5 and 10 μg. [34] Modification of factors can extend beyond affecting solubility, as shown in two studies by Erzurum et al[35] and Shireman et al[36], where two different mutations of FGF-1 reduce the susceptibility of the growth factor to cleavage by thrombin and thus extend its duration of bioactivity. This is especially important in drug delivery utilizing fibrin glue due to the high levels of thrombin used to form the gel.…”
Section: Loaded Factor Drug and Vector Systemsmentioning
confidence: 99%
“…R136K and R136K-CBD was constructed as described in our previous published protocols [16] [17]. In brief, R136K was generated using MORPH Site-Specific Plasmid DNA Mutagenesis Kit (5 Prime–3 Prime, Inc., Boulder, Co).…”
Section: Local Delivery Of a Collagen Binding Fgf-1 Chimera To Smoothmentioning
confidence: 99%
“…Thrombin can cleave FGF1; however, proteolytic cleavage of extracellular FGF1 can be prevented by its binding to heparan sulfate proteoglycans of the cell surface (Rosengart et al, 1988). Thus, for better detection of FGF1 released into the medium, we are using in our experiments the thrombin uncleavable FGF1R136K mutant (Erzurum et al, 2003;Duarte et al, 2006). Both vector control and sJ1 39-kDa transfectants exported FGF1 in response to temperature stress (42°C), whereas FGF1 release under nonstress conditions (37°C) was only observed in the sJ1 39-kDa NIH 3T3 transfectants ( Figure 3B).…”
Section: Sj1 39 Kda Induces Fgf1 Expression and Releasementioning
confidence: 99%